Real-time monitoring and analysis of hydraulic fracturing in surface well using microseismic technology: Case insights and methodological advances - Yanan Qian; Ting Liu; Cheng Zhai; Hongda Wen; Yuebing Zhang; Menghao Zheng; Hexiang Xu; Dongyong Xing; Xinke Gan (International Journal of Mining Science and Technology)
Through a case analysis, this study examines the spatiotemporal evolution of microseismic (MS) events, energy characteristics, volumetric features, and fracture network development in surface well hydraulic fracturing. A total of 349 MS events were analyzed across different fracturing sections, revealing significant heterogeneity in fracture propagation. Energy scanning results showed that cumulative energy values ranged from 240 to 1060 J across the sections, indicating notable differences. Stimulated reservoir volume (SRV) analysis demonstrated well-developed fracture networks in certain sections, with a total SRV exceeding 1540000 m3. The hydraulic fracture network analysis revealed that during the mid-fracturing stage, the density and spatial extent of MS events significantly increased, indicating rapid fracture propagation and the formation of complex networks. In the later stage, the number of secondary fractures near fracture edges decreased, and the fracture network stabilized. By comparing the branching index, fracture length, width, height, and SRV values across different fracturing sections, Sections No. 1 and No. 8 showed the best performance, with high MS event densities, extensive fracture networks, and significant energy release. However, Sections No. 4 and No. 5 exhibited sparse MS activity and poor fracture connectivity, indicating suboptimal stimulation effectiveness.